Analysis of the Influence of Location, Price, Hotel Reputation and Service Quality on Purchase Decisions at Santika Kelapa Gading Hotel - Livionara Verista Kurniawan (Syntax Idea)
The growth of the tourism sector in Indonesia shows very significant figures after the pandemic. As a result, the need for accommodation and MICE facilities continues to increase. This also has an impact on increasing the number of hotels, resulting in tight competition in the Indonesian market. This research aims to determine the influence of location, price, hotel reputation and service quality on purchasing decisions at the Santika Kelapa Gading Hotel. The hypothesis in this research will be tested quantitatively using SPSS. The sampling technique in this research is probability sampling using a simple random sampling approach by distributing questionnaires to a number of samples from the population list who are customers of the Santika Kelapa Gading hotel. The total sample of Santika Kelapa Gading hotel customers who filled out the questionnaire was 150 respondents. Based on the research results, it is known that there is no influence of location and price on purchasing decisions. However, there is a positive and significant influence of service quality and hotel reputation on purchasing decisions at the Santika Kelapa Gading hotel. The four factors of location, price, hotel reputation and service quality simultaneously influence purchasing decisions and have a moderate coefficient of determination. This means that these four variables have sufficient ability to be able to provide predictions or explanations of purchasing decision variables at Hotel Santika Kelapa Gading